What girls are made of - Bissett, Cora (Oberon modern plays., 2018)
It's 1992. In a small town in Fife, a girl is busting to get out into the world and see what's on offer. And an ad in the local paper declares: BAND SEEKS SINGER. Grunge has just gone global, scruffy indie kids are inheriting the earth, and a schoolgirl from Glenrothes is catapulted to a rock star lifestyle as the singer in a hot new indie band. Touring with Radiohead, partying with Blur, she was living the dream. Until she wasn't. Based on her meticulously detailed, pull-no-punches teenage diaries, this is the true story of Cora Bissett's rollercoaster journey from the girl she was to the woman she wanted to be.